Setting-up place-based and transdisciplinary research to foster agrifood system transformation: Insights from the Aliment'Actions project in western France - Berthet, Elsa T.; Gaba, Sabrina; Bombard, Cyrille; Goinard, Mathieu; Benvegnu, Nicolas; Fournout, Olivier; Bretagnolle, Vincent (Frontiers in Sustainable Food Systems, 2023)
Many agrifood systems around the world can be characterized as unsustainable. Research is increasingly required to inform the necessary radical transformations of the ways we produce, process, transport, and consume food. This article presents the research approach and methods of an ongoing project carried out at a long-term social–ecological research site, the Zone Atelier Plaine and Val de Sèvre (western France). The research project presented here, Aliment'Actions, started in 2018 and within 10 years of its implementation seeks to study and trigger transformation to enhance the sustainability and resilience of the regional agrifood system. Its research agenda contains four types of actions: (a) backdrop actions that enhance communication and trust between researchers and local stakeholders, (b) targeted actions that are conducted in specific villages with a wide range of stakeholders to elaborate and implement various transformation levers, (c) assessment actions evaluating the effects of different interventions, and (d) communication and result from dissemination actions. Overall, these actions aim to co-produce knowledge, raise awareness regarding challenges in the food system, envision new interactions between stakeholders, collectively generate innovative ideas, and catalyze actions oriented toward agrifood system transformation. The project implementation is adaptive and iterative, from theory to practice. This Methods paper puts this ongoing project into the perspective of other place-based research initiatives and provides insights on how to foster the engagement of non-academic actors in transdisciplinary research supporting agrifood system transformation.